KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU DAN MUTU PENDIDIKAN DI SDN 16 RUPAT - Syahrial (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
School action research is one of the studies conducted by school principals which aims to improve and improve the quality of education in the schools they lead. The main objective of this research was to improve teachers’ performance and education quality at SDN 16 Rupat. This research was conducted at SDN 16 Rupat, involving teachers as the research subjects. The results of this study were the principal's leadership had a significant influence on teachers’ performance and the education quality. It implied that the principal's leadership had been successfully implemented. The data from the observation analysis of teachers’ performance in the learning process obtained that the percentage for the discipline item was 87% while the percentage for the work performance item was 80.2%. Then, the percentage of the item was 75.4%, and it was 77.2% for the obedience to the rules. Next, the percentage for the responsibility item was 70.2%. It was seen that the overall average increased in teachers’ performance by 77.9%. Thus, it could be concluded that the principal's leadership effectively improved teachers’ performance and the education quality at SDN 16 Rupat.